Distribution and ecological drivers of spotted fever group rickettsia in Asia - Satjanadumrong, J; Robinson, M; Hughes, T; Blacksell, S (Springer, 2019)
Spotted fever group and related rickettsia (SFGR) are a neglected group of pathogens that belong to the genus Rickettsia. SFGR are zoonotic and are transmitted by arthropod vectors, primarily ticks, fleas and mites to accidental hosts. These emerging and re-emerging infections are widely distributed throughout the world. Land-use change and increasing human–wildlife conflict compound the risk of SFGR infection to local people in endemic areas and travelers to these regions. In this article, we discuss the rickettsial organisms causing spotted fever and related diseases, their arthropod vectors in Asia and the impact of land-use change on their spread.